KADER PROGRESIF UNTUK KEPEMIMPINAN MUHAMMADIYAH YANG VISIONER - Purnama Bahtiar, Asep (Tajdida: Jurnal Pemikiran dan Gerakan Muhammadiyah, 2015)
This article unravel how important progressive cadre to the next visionary Muhammadiyah leadership, according to the author in the context of today's Muhammadiyah leadership, especially with regard to its congress 47th in Makassar (3-8 August 2015) and post-congress later on, visionary and strategic leadership is very important and will be a plus for the leader. In addition will assist in planning and policy strategies, a visionary and strategic leadership are also needed for decision-making in the reality of the challenges and problems of the Muhammadiyah increasingly complex and diverse.